PERAN PEMERINTAH DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Goestyari Kurnia Amantha (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2021)
Way Urang Village is one of the villages in Padang Cermin District, Pesawaran Regency, which has natural resources in the form of natural hot springs. The potential of natural resources has not been developed and managed to the maximum extent possible to provide benefits and improve the welfare of the community. The purpose of this study was to see how the role of the village government in improving community welfare in the management of hot springs in Way Urang Village. The method used in this research is a qualitative descriptive research method. Data sources are obtained through interviews, observations and documentations. After the data is collected then analyzed for data reduction, data presentation and data verification. Based on the research results, the Government of Way Urang Village, Padang Cermin District, Pesawaran Regency has not been able to play a role as a stabilizer, innovator, pioneer, and modernizer in the management of Hot Springs in Way Urang Village. This is in line with the condition of community welfare where as a manifestation of community welfare, the improvement of living standards, increasing empowerment and enhancing freedom through the expansion of accessibility and choices of opportunities that are in accordance with human aspirations, capabilities and standards is not yet available. Those are due to the synergy absence among the community, the government village, and the local district government in the development, management and empowerment of Way Urang Village Hot Springs as the village's potential in improving community welfare.Keywords: Role, Village Government, Welfare.